Injury Profile in Swedish Elite Floorball: A Prospective Cohort Study of 12 Teams - Tranaeus, Ulrika (Sports Health, 2016)
BACKGROUND: Floorball is an indoor team sport with growing popularity worldwide characterized by rapid accelerations, decelerations, and cutting and pivoting movements. While injuries are common, there are few high-quality epidemiological investigations of floorball injuries. Therefore, the aim of this study was to determine the incidence and severity of injuries in male and female elite-level floorball players in Sweden. HYPOTHESIS: The incidence of injuries has not decreased; female players are more vulnerable to injury than male players. STUDY DESIGN: Prospective cohort study. LEVEL OF EVIDENCE: Level 3. METHODS: Twelve floorball teams (6 male, 6 female) in the Swedish premiere leagues were followed for 1 year (preseason, game season, and the entire year). The team medical staff reported injury incidence, location, type (traumatic or overuse), and severity. Differences between male and female players were analyzed using the Mann-Whitney U test. RESULTS: The injury incidence was greater in female players during preseason (22.9 vs 7.4, P = 0.01), game season (39.5 vs 28.3, P = 0.002), as well as the whole year combined (33.9 vs 20.8, P = 0.02). The thigh was the most common injury location in male players and the ankle in female players. Overuse injuries were more common among men and were primarily back problems. Traumatic injuries were more common in women—mainly knee and ankle injuries. Most injuries were of mild severity. A greater number of anterior cruciate ligament injuries occurred in women (n = 11) than in men (n = 2). CONCLUSION: The injury incidence was significantly greater in female floorball players throughout the entire floorball year. Male players sustained mostly overuse injuries while female players suffered traumatic injuries. The majority of injuries in floorball were mild, irrespective of player sex. CLINICAL RELEVANCE: Knowledge of the incidence and severity of floorball injuries is an essential step in the sequence of injury prevention. Future research should focus on identifying injury mechanisms and risk factors for these injuries to develop injury prevention strategies.